Analysis of temporal variation characteristics in water resources in typical ecosystems of the Genhe River Basin - 赵, 恺; 秦, 仓 富.; 岳, 杰 永.; 李, 龙; 董, 宇 晓.; 刘, 甫 林.; 李, 艳; 乌, 汉 义.; 贺, 嵘; 王, 倩 雅.; 徐, 洁 雅.; 乌, 拉 云. (Frontiers in Forests and Global Change, 2024)
The Genhe River Basin is an ecological barrier and water conservation area in northern China, but its hydrological process has undergone significant changes due to climate change and human activities, endangering ecosystem functions and water resource security. Systematic research on the influencing mechanisms and laws of hydrological processes in different ecosystems in this region remains lacking. Therefore, this study analyzed the effects of different anthropogenic factors on the hydrological processes of typical ecosystems in the Genhe River Basin. The Soil and Water Assessment Tool distributed hydrological model was used to simulate the surface runoff, evapotranspiration, and soil water content of the three ecosystems of forest, grassland, and farmland in four different periods of 1980, 1990, 2000, and 2010. The spatial and temporal changes in water resources in typical ecosystems under the influence of historical climate change were demonstrated. Results showed that under different land use scenarios, the surface runoff of the farmland ecosystem increased, the evapotranspiration remained unchanged, and the soil water content decreased. The surface runoff of forest and grassland ecosystems did not change significantly, the evapotranspiration increased, and the soil water content decreased. This study reveals the influence of different human factors on the hydrological processes of typical ecosystems in the Genhe River Basin and provides a scientific basis for water resources management and ecological protection in the region.